Lessson-Learned: Participatory Action Research Project with Upland Smallholder Farmers Practicing Cropland Agroforestry System in Wonogiri Regency to Support National Food Security - Rudy Nur Hidayah; Wiyono Wiyono; Oka Karyanto (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2021)
Indonesia government pays little attention to address impending threat of the existences of upland smallholder farmers due to insufficient farm income. This condition poses an imminent threat to national food security. One of the initiatives to address the condition is participatory action research project conducted by Faculty of Forestry UGM with 12 upland smallholder farmers in Wonogiri regency from 2016 to 2018. The result of the participatory action research project showed that although the 12 smallholder farmers practice cropland agroforestry system in marginal land, their increased rice production could improve farm income, be similar in rice field and support national food security. Therefore, this study aimed at investigating lesson-learned of the participatory action research project. This study was conducted on January-March 2020, used participant observation and semi-structure interview methods to collect data from the 12 smallholder farmers. After the collected data were analyzed by descriptive method, this study founded four points of lesson-learned including (1) finding a responsive smallholder farmer group; (2) minimizing negative role of local elite; (3) maximizing positive role of local elite; (4) implementing modified technology package.